Study of high-altitude cerebral edema using multimodal imaging - Long, Changyou; Bao, Haihua (Frontiers in Neurology, 2023)
Objective: To analyze the brain imaging features of high altitude cerebral edema (HACE) on CT and multi-sequence MRI, and to explore its injury characteristics. Materials and Methods: 30 patients with HACE diagnosed from January 2012 to August 2022 were collected as the experimental group, and 60 patients with dizziness from the plain to the plateau or from lower altitude to higher altitude in a short period of time were collected as the control group. The general clinical data of the experimental group were counted and classified according to clinical symptoms, and then head CT and multi-sequence MRI (T1WI, T2WI, FLAIR, DWI) were performed in both groups. Among them, 9 patients with HACE were also scanned by SWI. Finally, the images were analyzed. Results: 1. According to clinical symptoms, 30 cases of HACE were divided into mild in 12 cases and severe in 18 cases. There was no significant difference in sex, age, leukocyte, neutrophil and glucose content between mild and severe HACE. 2. The sensitivity and specificity of MRI diagnosis are 100% and 100% respectively, the sensitivity and specificity of CT diagnosis are 23.3% and 100%, respectively. 3. The distribution range of deep and juxtacortical white matter edema in severe HACE was significantly larger than that in mild HACE (p<0.001). 4. The distribution range of corpus callosum edema in severe HACE was significantly larger than that in mild HACE (p=0.001). 5. The ADC value of the splenium of corpus callosum in severe HACE was significantly lower than that in mild HACE (p=0.049). 6. In mild and severe HACE, the signal intensity of DWI sequence was significantly higher than that of conventional MRI sequences (T1WI, T2WI, FLAIR) (p=0.008, p=0.025, respectively). 7. In severe HACE, 7 cases showed bilateral corticospinal tract edema at the thalamic level, and SWI showed cerebral microbleeds (CMBs) in 5 cases, especially in the corpus callosum. Conclusions: MRI has more advantages than CT in the evaluation of HACE, especially in DWI sequence. The white matter injury of severe HACE is more severe and extensive, especially in corpus callosum, and some CMBs and corticospinal tract edema may also appear.